THE INFLUENCE OF THE CONCEPT OF PERSONAL SPACE ON VISITOR ACTIVITIES IN APSARI PARK SURABAYA - Amrullah, Alfian Rizkyananda; Firmansyah, Mochammad Hanif; Hakim, Luqman; Ferdiansyah, Aldi Candra; Ummah, Muchammad Widadul (ADBE, 2024)
The Analysis about the concept of personal space in Taman Apsari Surabaya is a relevant study in understanding the impact of design and spatial arrangement on visitor experiences in achieving a comfortable and calming personal space in a densely populated urban environment. This research aims to identify the concept of personal space in enhancing the level of satisfaction and quality of life of the local community. The research methods used include visitor surveys, field observations, and spatial design analysis. The results show that the concept of personal space in Taman Apsari Surabaya has the potential to provide significant benefits for visitors in terms of relaxation, social interaction, and mental well-being. However, there are several challenges that need to be addressed, including better management of visitor density, more flexible spatial arrangements, and improved accessibility for all segments of society. The application of this research can be used as a reference for the improvement of urban park design and management in the future, focusing on creating an inclusive, sustainable environment that supports the holistic well-being of urban communities.